How to take the Supremo Tribunal Federal (brazilian Federal Supreme Court) seriously: on the suspension of advance claim rights’ concession n.91 - Chueiri, Vera Karam de (2009)
This article aims at analyzing the suspension by Brazilian Federal Supreme Court of the suspension of advance claim rights' concession n.91 under the perspective of Ronald Dworkin’s theory, concerning the understanding that it is necessary for judiciary power to have a critical and constructive (political) attitude in order to decide, especially for constitutional courts. In this sense, every decision rendered by the court in favor of a fundamental right must prevail, once it is founded on arguments of principle and it is coherent with the constitutional system.  There, it follows the idea that there are right answers in law and that these are better than those offered by legal conventionalism or legal pragmatism. Then, it also follows the question about the legitimacy of the court, that is, does the Supremo Tribunal Federal should have the last word on decisions of the executive and legislative powers, especially concerning their public policies?